(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
Public satisfaction assessment of legal services is an important indicator for improving the quality of public service. The Tapaktuan District Attorney’s Office requires a system that can measure public satisfaction objectively and systematically. This study aims to design and develop an information system for evaluating legal service satisfaction using the Rating Scale and Multi-Attribute Utility Theory (MAUT) methods. The rating scale is used to assign scores to five criteria: service speed, service friendliness, staff competency, report handling process, and facility comfort. The assessment results are then analyzed using MAUT to obtain overall satisfaction rankings. The system is developed as a web-based application for easy access by staff and the public. Respondent samples are selected proportionally and representatively, including the general public, complainants/defendants, witnesses, lawyers, and employees who have received legal services, using accidental sampling during the survey period, with 30 respondents to ensure data representativeness. From five criteria, three alternatives, and 30 respondent samples, the final score obtained is 4.51, indicating a “very satisfied” level for Case Reporting Services. This system is expected to assist the Tapaktuan District Attorney’s Office in evaluating and improving the quality of legal services consistently.